Climate change financial risks: Pricing and portfolio allocation - Christos Karydas; Anastasios Xepapadeas (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
There are concerns that climate-related physical and political risks are not yet properly reflected in asset prices. To address these concerns, we develop a dynamic asset pricing framework with two sources of rare disasters: macroeconomic events and climate change. We link carbon emissions and portfolio composition with the stochastically-varying probability of climate-related events. Using theory and simulations we study the implications of the imminent threat of climate change on different market measures and on the participation of carbon-intensive assets in the market portfolio. We also obtain closed-form solutions for market prices and the Social Cost of Carbon. Our results suggest that climate change implies a positive and increasing risk premium. We also show that, with the observed trends in climate change, macroeconomic risk works as a hedge against catastrophic climate change, such that the aggregate equity premium may remain unaltered. The transition risk of climate policy substantially lowers the participation of carbon-intensive assets in the market portfolio.
Keywords: G11; G12; O44; Q51; Q54; 330; Climate change; Risk premia; Rare events; Policy Risk; Stranded assets